Penerapan Siklus DMAIC (Define, Measure, Analyze, Improve and Control) dengan Menggunakan Metode Taguchi untuk Meningkatkan Kualitas Bir Pletok dengan Penambahan Cabe Jawa : (Studi Kasus UMKM Bir Pletok Bang Udin) - Muhammad Izaz Ammar; Deny Wibisono; Puji Suharmanto (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Quality Management has been known since four thousand years ago, when the ancient Egyptians measured the dimensions of the stones used to build the pyramids. In modern times, quality management activities have developed through several activities, namely inspection, quality control, quality assurance, quality management and integrated quality management. The problem currently occurring at Bir Pletok Bang Udin UMKM in quality management is that they do not know the right composition to increase quality and do not know the standard level of factors used, so the author has carried out quality improvements in product manufacture. This research uses the DMAIC cycle (Define, Measure, Analyze, Improve and Control) with the Taguchi method for quality improvement. The aim of this research is to combine the DMAIC cycle with the Taguchi method to improve the taste quality of beer pletok drinks. The results of this research are that there is a significant change in the DPMO value and sigma value, before the DPMO improvement was 614.092 and the sigma value was 1.21, this value was relatively low, after the improvement the DPMO value became 32, this proves that the number of defects has decreased and the sigma value has increased to 5.50 This proves that there has been a large increase in process capability, so that the improve phase has proven to be very effective in improving quality and process capability.